Synthesis and Structure of 4-Substituted (1S,9aR)-1-[(1,2,3-triazol-1-yl)methyl]octahydro-1H-quinolysines of Lupinine - Nurmaganbetov, Zh.S.; Fazylov, S.D.; Turdybekov, K.M.; Nurkenov, O.A.; Turdybekov, D.M.; Mukusheva, G.K.; Minayeva, Ye.V.; Khabdolda, G. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The article presents results on the synthesis and investigation of the structural features of a number of 1,4-disubstituted 1H-1,2,3-triazole derivatives of the alkaloid lupinine. Lupinine modification reactions have been carried out at the hydroxymethylene group in the C-1 position of the quinolysine backbone. It has been shown that (octahydro-2H-quinolysine-1-ylmethyl)methanesulfonate in high yield (93%) is formed by the in-teraction of lupinine with methanesulfonyl chloride in methylene chloride. Subsequent treatment of this com-pound with sodium azide in dimethylformamide on heating leads to the formation of 1-(azidomethyl)octahydro-2H-quinolysine in 61% yield. It has been found that the reaction of a new azide with terminal alkynes of various nature in the presence of aqueous СuSO4 and sodium ascorbate in dimethylfor-mamide can form the corresponding 4-substituted (1S,9aR)-1-[(1,2,3-triazol-1-yl)methyl]octahydro-1H-quinolysines. New 1,2,3-triazole derivatives of lupinine containing various aryl substituents at the C-4 posi-tion of the triazole ring have been obtained. The high selectivity of the reaction is explained by the action mechanism of the Sharpless catalyst. The spatial structure of the molecules of lupinine methanesulfonate, 4-aryltriazolylmethyl-octahydroquinolysines has been established by X-ray diffraction analysis. X-ray structur-al analysis data of new compounds have been deposited in the form of CIF files at the Cambridge Crystallo-graphic Data Center
Лупининнің 4-орынбасылған (1S,9aR)-1-[(1,2,3-триазол-1-ил)метил]- октагидро-1Н-хинолизиндерінің синтезі және құрылысы
Синтез и строение 4-замещенных (1S,9aR)-1-[(1,2,3-триазол- 1-ил)метил]октагидро-1Н-хинолизинов лупинина
Keywords: quinolysine alkaloids; lupinine; azides; triazoles; methanesulfonyl chloride; terminal alkynes; 1,3-dipolar cycloaddition reaction; X-ray structural analysis